Comparison of subcritical CO2 and ultrasound-assisted aqueous methods with the conventional solvent method in the extraction of avocado oil - Tan, Chin Xuan; Chong, Gun Hean; Hamzah, Hazilawati; Mohd Ghazali, Hasanah (Elsevier, 2018)
Avocado (Persiana americana Mill) belongs to the Lauraceae family. High level of lipids in the avocado pulp can be served as an important raw material for edible oil extraction. In the present study, the physicochemical properties of avocado oil extracted using subcritical CO2 extraction (SCO2) and ultrasound-assisted aqueous extraction (UAAE) were compared with the conventional solvent extraction. In comparison to solvent extraction, the oils extracted using SCO2 and UAAE were found to have higher iodine values, but lower slip melting points, free fatty acid contents and saponification values. Regardless of the extraction methods, the major fatty acids in avocado oils were oleic (40.73-42.72%) and palmitic (28.12-34.48%) acids whereas the major triacylglycerols in avocado oils were palmitoyl-dioleoyl-glycerol (POO; 22.48-23.01%) and palmitoyl-oleoyl-linoleoyl-glycerol (POL; 17.64-18.23%). SCO2 and UAAE are effective “solvent-free” methods to extract avocado oils and potentially other edible oils.